Carbazole‐Based Tetrapodal Anchor Groups for Gold Surfaces: Synthesis and Conductance Properties. (27th November 2019) - O'Driscoll, Luke J.; Wang, Xintai; Jay, Michael; Batsanov, Andrei S.; Sadeghi, Hatef; Lambert, Colin J.; Robinson, Benjamin J.; Bryce, Martin R.
Abstract: As the field of molecular‐scale electronics matures and the prospect of devices incorporating molecular wires becomes more feasible, it is necessary to progress from the simple anchor groups used in fundamental conductance studies to more elaborate anchors designed with device stability in mind. This study presents a series of oligo(phenylene‐ethynylene) wires with one tetrapodal anchor and a phenyl or pyridyl head group. The new anchors are designed to bind strongly to gold surfaces without disrupting the conductance pathway of the wires. Conductive probe atomic force microscopy (cAFM) was used to determine the conductance of self‐assembled monolayers (SAMs) of the wires in Au–SAM–Pt and Au–SAM–graphene junctions, from which the conductance per molecule was derived. For tolane‐type wires, mean conductances per molecule of up to 10 −4.37 G0 (Pt) and 10 −3.78 G0 (graphene) were measured, despite limited electronic coupling to the Au electrode, demonstrating the potential of this approach. Computational studies of the surface binding geometry and transport properties rationalise and support the experimental results. Abstract : Vierbeinige Freunde : Selbstorganisierte Monolagen aus molekularen Drähten mit neuartigen Verankerungseinheiten bestehend aus vier Thiomethylgruppen wurden auf Gold gebildet und auf ihre Leitfähigkeit gemessen. Die tetrapodalen Anker bieten eine effektive Bindung, tragen aber nur minimal zum Leitwert der Drähte bei. Oberflächenbindung und elektronische Kopplung können daher unabhängig voneinander betrachtet werden.